Exploring the relationship between emotion regulation, inhibitory control, and eating psychopathology in a non‐clinical sample - Ramos, Rita; Vaz, Ana Rita; Rodrigues, Tânia F.; Baenas, Isabel; Fernández‐Aranda, Fernando; Machado, Paulo P. P. (European eating disorders review, 2024)
© 2023 Eating Disorders Association and John Wiley & Sons Ltd. Objective: The present study aimed to explore the relationship between difficulties in emotion regulation and deficits in inhibitory control, and the role of these processes in eating psychopathology in a non-clinical sample. We also explored the specificity in which deficits in inhibitory control may underlie eating psychopathology, namely whether they can be conceptualised as context specific or more extensive in nature. Method: Participants were 107 healthy individuals recruited at a major Portuguese university, aged between 18 and 43 years-old (M = 21.23, SD = 4.79). Two computerised neuropsychological tasks (i.e., emotional go/no-go and food go/no-go tasks) were used to assess response inhibition in the presence of general versus context-specific stimuli. A set of self-report measures was used to assess variables of interest such as emotion regulation and eating psychopathology. Results: Results indicated higher response inhibition deficits among participants with higher difficulties in emotion regulation comparing to those with lower difficulties in emotion regulation, particularly in the context of food-related stimuli. In addition, the relationship between difficulties in emotion regulation and eating psychopathology was moderated by inhibitory control deficits in both the context of food and pleasant stimuli. Conclusions: The present findings highlight inhibitory control as an important process underlying the relationship between difficulties in emotion regulation and eating psychopathology in non-clinical samples. Findings have important implications for clinical practice and the prevention of eating psychopathology in healthy individuals and individuals with eating disorders. This work was conducted at the Psychology Research Centre (PSI/01662), School of Psychology, University of Minho, and partially supported by the Portuguese Foundation for Science and Technology (FCT) and the Portuguese Ministry of Science, Technology and Higher Education (UID/PSI/01662/2019), through the national funds (PIDDAC); a grant by the FCT and the Portuguese Ministry of Science, Technology and Higher Education through national funds and co-financed by FEDER through COMPETE2020 under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-028145/PTDC/PSI-ESP/28145/2017) to Paulo Machado; and a PhD studentship granted to the first author (2022.12203.BD), supported by the FCT, funded with allocations from the State Budget of the Ministry for Science, Technology and Higher Education and with allocations from the European Social Fund.